Influence of Number of Implants and Connection Systems on Stress Behaviour of Mandibular Implant-retained overdentures: Photoelastic and Strain Gauge Analysis - Campaner, Marcio [UNESP]; Mendes Borges, Anna Clara [UNESP]; Camargo, Danielle de Almeida [UNESP]; Mazza, Leticia Cerri [UNESP]; Bitencourt, Sandro Basso [UNESP]; Medeiros, Rodrigo Antonio de; Goiato, Marcelo Coelho [UNESP]; Pesqueira, Aldieris Alves [UNESP] (Premchand Shantidevi Research Foundation, 2019)
Introduction: The consensus statement recommends at least two implants to support a mandibular overdenture for edentulous patients. However, to reduce cost and time of treatment, the concept of single implant-retained overdentures provides another option. Nonetheless, the optimal number of implants required to retain a mandibular overdenture is still under evaluation. Aim: To evaluate the biomechanical behaviour of overdentures supported by 1 or 2 implants with different types of connections and submitted to compression, by using Photoelastic (PA) and Strain Gauge Analysis (SGA). Materials and Methods: Based on one cast of an edentulous mandible, the specimens were divided in four groups of one specimen each for the PA and four groups of five specimens each for the SGA, divided by the type of connection (morse taper and external hexagon) and the number of implants (1 or 2). For PA, the photoelastic implant/prosthesis cast assembly was positioned in a circular polariscope associated with a universal testing machine (DL3000, INSTRON/EMIC) applying compression. The tension generated was photographed and analysed qualitatively (number of high-intensity (pink-green transition) and moderate (green/red) fringes). For SGA, two strain gauges were positioned on the mesial and distal aspect of each implant and the electrical signals were captured by a data acquisition device (ASD2001). The data were submitted to three-Way ANOVA and the Bonferroni Test (alpha=0.05) as post-hoc test for multiple comparisons. Results: Through PA, the greatest number of tension fringes in both connection types was presented by the two-implant supported overdentures when compared with the single-implant supported overdentures. Through SGA, a statistical difference was verified between the connections in groups with one implant (p<.001), with the morse taper having the lowest microstrain values. The lowest tension values in both types of connections were presented by the overdentures with one implant (p<.001). Conclusion: It was concluded that the number of implants directly influenced the distribution of tension in both forms of analysis, being greater for the overdentures supported by two implants. In addition, biomechanically, the single-implant mandibular overdentures may be suggested as an alternative treatment modality for the rehabilitation of edentulous patients, principally when being used with the morse taper system.
Keywords: Implant supported denture; overlay denture; Prosthesis failure analysis